Introduction to Islamic banking and finance : principles and practice - Hassan, M. Kabir; Kayed, Rasem N.; Oseni, Umar Aimhanosi (Pearson Education Limited, 2013)
Islamic banking and finance is becoming one of the most significant aspects of the modern global financial system. Why? Because it is a fast-growing industry that has developed rapidly within a few years from a niche industry to a global force to be reckoned with in the international arena. However, with the worldwide spread of Islamic financial products and the growing interest of students and financial experts in Islamic finance, numerous books,monographs, and academic articles are being produced to explain the significance of this new industry to the global financial system. Nevertheless, there has not been much focus on a professional textbook on Islamic banking and finance for students of higher education who require case studies and practical examples in their programs. This seemingly neglected aspect of Islamic financial literature is the gap that this book seeks to fill, focusing on the principles and practice of Islamic banking and finance in the modern world. In this dynamic industry, there is a need to present a textbook for the ever-increasing academic and professional institutions offering Islamic finance as a course.